PEMODELAN DAN PERAMALAN JUMLAH PENGUNJUNG KBS MENGGUNAKAN MODEL VARIASI KALENDER ARIMAX - Arifani, Indry; Rahmayanti, Weny; Putri, Tesalonika; Kurniasari, Vira Oktavia; Anky, Alicia Mutiara (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Surabaya zoo (KBS) is one of zoo in Indonesia, which has benefits as a wildlife conservation and educational tours so that its existence is needed. Then research is held for predicting number of the Kebun Binatang Surabayaâs visitors in the future. The forecast results are used as a reference and recommendation by the manager of Kebun Binatang Surabaya in making the determination of policy and long-term development. Forecasting has been made by applying ARIMAX calendar variation model and the results are used to determine potential future KBS as The Biggest Zoo In South East Asia. The data used is about the number of visitors per month, start at January 2005 to December 2013, analysis was performed using the Box-Jenkins ARIMA models for estimating the order and Variations Calendar to capture seasonal patterns measured in calendar hijriyah (non-masehi).Â Keywords: Â Box-Jenkins, Kebun Binatang Surabaya, Forecasting, Variations Calendar